An Analysis of Students’ Mathematical Curiosity in Online Learning Viewed from Academic Level and Gender - Zetriuslita, Zetriuslita; Saleh, Sitti Fithriani; Baharullah, Baharullah; Laelasari, Laelasari (Research in Social Sciences and Technology, 2024)
Online learning affects students' curiosity, so it is important to develop students' curiosity during the pandemic. The purpose of this study is to describe and analyze students' curiosity about online learning. This study was conducted in the Department of Mathematics Education during the odd semester 2021/2022 with 106 students in three different courses. The research instrument was a mathematical curiosity questionnaire administered to students using the Google Documents application. The data analysis technique used was descriptive analysis. The results showed that the general curiosity of the students is classified as "strong" with a percentage of 75.17%. Academically, students with low, medium and high curiosity are considered strong with percentages of 74.07 percent, 76.5 percent and 75.12 percent. Measured by gender differences, the proportion of male and female students is 76.43 and 77.5 percent. Data analysis showed that in the era of the Covid-19 pandemic, curiosity about learning mathematics does not depend on the academic level of online learning or on gender differences. The effect of the result that the students during the Covid-19 pandemic, mathematical curiosity is still used in online learning and should be improved. This research contributes to the growing body of knowledge on mathematical learning in the digital age and offers practical recommendations for fostering mathematical curiosity in online.